2009
DOI: 10.1016/j.ijheatmasstransfer.2008.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of surface dryout near heating surface at high heat fluxes in subcooled pool boiling

Abstract: The authors have conducted measurements of liquid-vapor behavior in the vicinity of a heating surface for saturated and subcooled pool boiling on an upward-facing copper surface by using a conductance probe method. A previous paper [A. Ono, H. Sakashita, Liquid-vapor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…They reported that the bubble growth rate becomes slower with increasing pressure and it is approximately expressed as R p / t 0:2 at 1.5 MPa; this relation is quite different from Eqs. (1) and (2)…”
Section: Results Of Bubble Growth Rates 1 Previous Studies On Pmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported that the bubble growth rate becomes slower with increasing pressure and it is approximately expressed as R p / t 0:2 at 1.5 MPa; this relation is quite different from Eqs. (1) and (2)…”
Section: Results Of Bubble Growth Rates 1 Previous Studies On Pmentioning
confidence: 99%
“…The results obtained in these three papers [1][2][3] suggest that, at least for boiling at atmospheric pressure, the trigger mechanism of the DNB-type CHF is explained comprehensively based on the macrolayer dryout model proposed first by Katto and Yokoya,4) where the CHF occurs due to the dryout of the macrolayer beneath the large vapor masses.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…No coating for electrical insulation was provided on the surface of the probe tip, but it has been confirmed that the probe is able to measure liquidvapor behaviors with high accuracy. 23) The conductance probe was connected to a moving stage with an accuracy of 0.5 mm in the direction normal to the heating surface. During the measurements, potassium chloride (KCl) was added to the water to increase the electroconductivity of the water, and the AC voltage was imposed between the heating surface and the probe.…”
Section: Measurement System With Conductance Probementioning
confidence: 99%
“…A liquid-rich zone between vapor masses and a heating surface is usually termed a 'macrolayer', and the authors here also used the term 'macrolayer' in previous papers [11,14]. As shown below, however, the liquid-rich zone is able to reach 1mm in thickness for 2-propanol/water mixtures, and it may be inappropriate to call this a macrolayer, which could be associated with a thin liquid-layer of tens to a few hundreds micrometers.…”
Section: Introductionmentioning
confidence: 99%